(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article reveals the lexicographic analysis of agrarian terms in Uzbek and Russian languages. The special term of each field is considered as a system of naming concepts, and this scientific article is shown as a means of expressing agricultural terms. The article is devoted to the lexicographical comparative analysis of the terms of the agrarian system in Russian and English.